Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.orglett.8b03679
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Photosensitizer-, Metal-, and Base-Free Visible-Light-Promoted C–H Thiolation via Reverse Hydrogen Atom Transfer

Abstract: Visible-light-driven, intramolecular C­(sp2)–H thiolation has been achieved without addition of a photosensitizer, metal catalyst, or base. This reaction induces the cyclization of thiobenzanilides to benzothiazoles. The substrate absorbs visible light, and its excited state undergoes a reverse hydrogen-atom transfer (RHAT) with 2,2,6,6-tetramethylpiperidine N-oxyl to form a sulfur radical. The addition of the sulfur radical to the benzene ring gives an aryl radical, which then rearomatizes to benzothiazole vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…In 2019, Li, Lang, and co-workers reported a novel visible-light-promoted intramolecular C-H thiolation of thiobenzanilides 41 to give benzothiazoles 24 under exogenous photosensitized-, metal-, and base-free conditions (Table 4, entry 9). 55 The visible-light-driven reaction occurred smoothly only in the presence of 2.0 equiv TEMPO in CHCl 3 . The reaction mechanism proposed that the substrate absorbs visible light to form its excited state, which undergoes a reverse hydrogen-atom transfer (RHAT) with TEMPO Noxyl to give a sulfur radical.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…In 2019, Li, Lang, and co-workers reported a novel visible-light-promoted intramolecular C-H thiolation of thiobenzanilides 41 to give benzothiazoles 24 under exogenous photosensitized-, metal-, and base-free conditions (Table 4, entry 9). 55 The visible-light-driven reaction occurred smoothly only in the presence of 2.0 equiv TEMPO in CHCl 3 . The reaction mechanism proposed that the substrate absorbs visible light to form its excited state, which undergoes a reverse hydrogen-atom transfer (RHAT) with TEMPO Noxyl to give a sulfur radical.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…In coordination chemistry, pincer-type ligands containing thio-amide motif have already exhibited their 4 incomparable chelating ability to the selected transition-metals, and their corresponding complexes have been applied in various areas such as chemical-sensor materials, tunable redox-potential complexes, polymer hybrid luminescence materials, building blocks for multinuclear com-plexes, and catalysts for cross-coupling reactions [23][24][25][26][27][28][29][30]. The thio-substitution of amides with LR is an efficient and straightforward method, either the availability of amide substrates, LR, or the reaction condition [7,8,[31][32][33][34][35]. With thio-substitution of amides as a model, we herein reported an efficient work-up procedure of applying LR by utilizing ethylene glycol to decompose the compound A (Figure 2).…”
Section: Figure 1 Generation Of the Six-membered By-product Amentioning
confidence: 99%
“…27 Very recently, we found that thiobenzanilide derivatives can absorb visible light, and their photoexcited states undergo cyclization to benzothiazoles using stoichiometric 2,2,6,6-tetramethylpiperidine N-oxyl as the hydrogen atom transfer reagent. 28 The oxidative conversion required a relatively expensive oxidant and displayed low positional selectivity. For meta-substituted thioanilides, a mixture of two regioisomers was formed.…”
mentioning
confidence: 99%
“…In 2017, Miyake et al developed a visible-light-promoted protocol for C­(sp 2 )–S cross coupling of thiols and aryl halides via intermolecular charge transfer without photoredox catalysts and transition-metal catalysts . Very recently, we found that thiobenzanilide derivatives can absorb visible light, and their photoexcited states undergo cyclization to benzothiazoles using stoichiometric 2,2,6,6-tetramethylpiperidine N -oxyl as the hydrogen atom transfer reagent . The oxidative conversion required a relatively expensive oxidant and displayed low positional selectivity.…”
mentioning
confidence: 99%